2022
DOI: 10.3390/nu14112245
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Supplementation Affects Skin Wound Healing in a Rat Model

Abstract: Polyunsaturated fatty acids (PUFA) play an important role in reparative processes. The ratio of PUFAs n-3 to n-6 may affect wound healing. The study aimed to evaluate the effect of dietary supplementation with n-3 and n-6 PUFA in two proportions on skin wounds in laboratory rats. Adult male Wistar rats received 20% fat emulsion with a ratio of 1.4:1 (group A) or 4.3:1 (group B) for n-3:n-6 PUFAs at a daily dose of 1 mL/kg. The control group received water under the same conditions. The animals were supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Similarly, studies investigating the effect of oleic acid on inflammation have put in evidence an anti-inflammatory effect induced by an increase in IL10 levels and a reduction in COX-2 levels [28]. This is in line with the improvement of skin wound healing that was observed in rats following supplementation with fatty acids [49] and with findings of topical oleic acid anti-inflammatory activity [50]. However, other authors have found a high expression of pro-inflammatory TNF and IL-17 in oleic acid-treated wounds [28].…”
Section: Thiobarbituric Acid (Tba) Assay Resultsmentioning
confidence: 55%
“…Similarly, studies investigating the effect of oleic acid on inflammation have put in evidence an anti-inflammatory effect induced by an increase in IL10 levels and a reduction in COX-2 levels [28]. This is in line with the improvement of skin wound healing that was observed in rats following supplementation with fatty acids [49] and with findings of topical oleic acid anti-inflammatory activity [50]. However, other authors have found a high expression of pro-inflammatory TNF and IL-17 in oleic acid-treated wounds [28].…”
Section: Thiobarbituric Acid (Tba) Assay Resultsmentioning
confidence: 55%
“…In general, the literature suggests that the anti-inflammatory action of ω-3 PUFA requires a minimal administration period of 14 days, and that the prophylactic supplementation for the same period increases EPA and DHA levels in the cell membrane. Consequently, the cell membrane becomes robust and resistant to lysis [ 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs), which mainly comprise omega-3 and omega-6 fatty acids, can regulate the immune response and participate in skin wound healing, repair, and tissue remodelling [ 58–60 ]. In diabetic rat skin wound healing models, omega-3 PUFAs have been found to alter proinflammatory cytokine production, which substantially decreased the number of grade three mast cells on days 3 and 5 and the wound area by day 7 [ 61 ].…”
Section: Reviewmentioning
confidence: 99%